2016
DOI: 10.1109/jbhi.2015.2391671
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of an Interactive Exercise Coaching System for Older Adults: Lessons Learned

Abstract: Although the positive effects of exercise on the well-being and quality of independent living for older adults are well-accepted, many elderly individuals lack access to exercise facilities, or the skills and motivation to perform exercise at home. To provide a more engaging environment that promotes physical activity, various fitness applications have been proposed. Many of the available products, however, are geared toward a younger population and are not appropriate or engaging for an older population. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 27 publications
2
83
0
3
Order By: Relevance
“…Seven studies investigated the effect of gaming/VR exercise on gait parameters (63)(64)(65)(66)(67)(68)(69), and six studies examined the effectiveness with regard to different physical functions and associated fall risk (10,(70)(71)(72)(73)(74). The remaining 12 studies investigated the feasibility of using gaming/VR exercise to increase physical activity in healthy older adults (75)(76)(77)(78)(79), in hospitalized older adults (80,81), or in a patient population (82)(83)(84)(85)(86).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies investigated the effect of gaming/VR exercise on gait parameters (63)(64)(65)(66)(67)(68)(69), and six studies examined the effectiveness with regard to different physical functions and associated fall risk (10,(70)(71)(72)(73)(74). The remaining 12 studies investigated the feasibility of using gaming/VR exercise to increase physical activity in healthy older adults (75)(76)(77)(78)(79), in hospitalized older adults (80,81), or in a patient population (82)(83)(84)(85)(86).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies reported that length of intervention was determined by either the individual participant's physical therapy treatment (49), or phase of dopaminergic medication (85). Three studies did not report on intervention frequency (49,51,62), and three studies did not report on intervention duration (44,62,79). Finally, one study had optional duration (60), and one study had self-regulated duration and frequency of each exercise session (71).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the supervised therapy session is done within a short period of time mainly due to economical reasons. In order to support and maintain the rehabilitation of stroke survivors, continuous home based therapy systems are being investigated [Langhorne et al, 2005, Zhou and Hu, 2008, Sucar et al, 2010, Hondori et al, 2013, Mousavi Hondori and Khademi, 2014, Chaaraoui et al, 2012, Ofli et al, 2016. Having these systems at home and easily accessible, the patients keep a good level of motivation to do more exercise.…”
Section: Introductionmentioning
confidence: 99%